Категорія духовно-морального виховання учнівської молоді в історії вітчизняної педагогічної думки - Ворожбіт, Вікторія Вікторівна (НТУ "ХПІ", 2011)
In the article the analysis of component lexical construction of spiritual-moral education of pupils in general schools is conducted, concordance of lexemes "spiritual", "spirituality", "moral", "morality" is done. The structure of object and functions of spiritual-moral education of pupils is exposed on such approaches: materialistic, idealistic, symbiotic.
Keywords: духовність; моральність; виховання; освіта; школа